Experiences in Assessment of Students in a Large-scale Digital Literacy Programme at a Higher Institution of Learning (International Journal of Psychosocial Rehabilitation, 2020)
The research on which this paper is based focused on the assessment processes within a large-scale Digital Academic Literacy (DAL) Program at the University of the Western Cape, integrated into modules across faculties and departments. Between 2005 and 2015, the team engaged in traditional, manual assessment methods. This paper deliberates the overall traditional assessment methods that enabled the team to deliver and support 3,601 students across 17 departments in the 2015 academic year. A qualitative research design, with supporting quantitative statistics, was adopted. Key findings include an extensive, challenging, blended learning approach that enabled facilitators to continue with delivery via various modes, including the institutional learning management system (LMS) that hosts screencasts and student-led discussion forums, email boxes, and face-to-face consultations. These findings presented a tedious manual assessment process that demands the DAL program transform into the application of an eAssessment Tool that would improve, digitize, and enhance assessment processes.